2023
DOI: 10.1177/11206721231218656
|View full text |Cite
|
Sign up to set email alerts
|

Microvascular changes after pars plana vitrectomy for rhegmatogenous retinal detachment repair: A comparative study based on gas tamponade agent

Genovefa Machairoudia,
Dimitrios Kazantzis,
Irini Chatziralli
et al.

Abstract: Purpose The purpose of this study was to investigate the effect of gas tamponade on microvascular changes in patients with rhegmatogenous retinal detachment (RRD), who underwent pars plana vitrectomy (PPV), using optical coherence tomography angiography (OCTA). Methods Participants in this study were 48 patients with RRD, who were treated with PPV and gas tamponade without internal limiting membrane peeling. All participants underwent slit-lamp examination, fundoscopy, spectral domain-optical coherence tomogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Additionally, a negative correlation between the final postoperative BCVA and FAZ area in both SCP [18,21] and DCP [18] was observed. A recent study published by Machairoudia et al [35] found significant changes in the foveal avascular zone in the superficial and deep capillary plexus at 6 months between operated eyes compared to fellow eyes with a moderate correlation with BCVA, and no significant differences in vessel density were observed.…”
Section: Discussionmentioning
confidence: 83%
“…Additionally, a negative correlation between the final postoperative BCVA and FAZ area in both SCP [18,21] and DCP [18] was observed. A recent study published by Machairoudia et al [35] found significant changes in the foveal avascular zone in the superficial and deep capillary plexus at 6 months between operated eyes compared to fellow eyes with a moderate correlation with BCVA, and no significant differences in vessel density were observed.…”
Section: Discussionmentioning
confidence: 83%
“…While it was conducted at a single center with a relatively modest sample size and a brief follow-up period, mirroring the scope of many surgical studies in this domain, it is important to highlight that we examined 44 eyes affected by macula off RRD. This sample size surpasses that of comparable studies [31][32][33][34][35][36][37][38][39]. Inherent to the studied pathology, the inability to determine the preoperative OCTA parameters in eyes with macula off RRD limited the metrics comparison after surgery.…”
Section: Discussionmentioning
confidence: 94%
“…Woo et al [32] reported that FAZ was negatively correlated with BCVA after RRD repair in both macula-on and macula-off eyes. Machairoudia et al [33] found significant changes in the foveal avascular zone in the superficial and deep capillary plexus at 6 months between operated eyes compared to fellow eyes with moderate correlation with BCVA, and no significant differences in vessel density were observed.…”
Section: Discussionmentioning
confidence: 95%